President’s Message - Ferguson, Cathleen (Operating Room Nurses Association of Canada Journal, 2020)
As 2020 comes to a close we reflect back on what has been a unique and challenging year in both our personal and professional lives. These have been unprecedented times that have caused us to draw on many strengths & qualities. One of those strengths is flexibility. Perioperative nurses across Canada have certainly exhibited this quality as we navigate through this pandemic.